2019
DOI: 10.1111/lre.12283
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrology on water quality and trophic state of irrigation reservoirs in Sri Lanka

Abstract: Many reservoirs provide multiple benefits to people around the world, in addition to primary uses such as irrigation. Thus, reservoir management should address their multiple uses. The water quality of ten irrigation reservoirs in Sri Lanka was examined in the present study with the objective of better understanding the effects of hydrological regimes on reservoir water quality and trophic state. Basic limnological parameters pertinent to the nutrient loads to, and trophic state of, the reservoirs were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Results also revealed that the Z SD was generally highest during the SIM and NEM (October to February) seasons, which could reflect the occurrence of the highest precipitation, and on the contrarywise lowest during the driest SWM (May to September) season. These findings were similar to what other researchers have found at the reservoir scale [14,16]. Many studies reported that wind-driven sediment resuspension negatively impacts water transparency and is generally more prevalent among shallow reservoirs of Sri Lanka [14,56,57].…”
Section: Surface Water Transparency and Driving Forcessupporting
confidence: 91%
See 2 more Smart Citations
“…Results also revealed that the Z SD was generally highest during the SIM and NEM (October to February) seasons, which could reflect the occurrence of the highest precipitation, and on the contrarywise lowest during the driest SWM (May to September) season. These findings were similar to what other researchers have found at the reservoir scale [14,16]. Many studies reported that wind-driven sediment resuspension negatively impacts water transparency and is generally more prevalent among shallow reservoirs of Sri Lanka [14,56,57].…”
Section: Surface Water Transparency and Driving Forcessupporting
confidence: 91%
“…Direct influences are determined according to the population density [59], while indirect impacts are in the form of human-induced land-use changes, which influence sediment delivery, algal production, and vegetation cover [60,61]. According to the previous findings, population density has a significant influence on the rapid deterioration and degradation of the quality of surface water in Sri Lanka as the transparency is directly affected by the rate of sewage collection within the catchment [16,38]. This study also showed that the influence of the population was a significant factor in all zones.…”
Section: Surface Water Transparency and Driving Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using 17 published food web models of 13 African lakes as a case study, Gownaris et al (2018) reported that water-level fluctuations are a key process influencing ecosystem structures and functions in lakes. Furthermore, in a parallel study the RRLF of the same 10 reservoirs in the present study was found to positively influence the reservoir trophic status (Nadarajah et al, 2019). Although biological F I G U R E 5 CCA loading plots for phytoplankton (•), 10 study reservoirs (∆) and physicochemical parameters (lines; reservoir abbreviations given in Figure 1; physical, chemical and biological parameters codes given in Table 2; phytoplankton taxa codes given in productivity-related water quality parameters exhibited some relationships with RRLF (Figure 4).…”
Section: Discussionsupporting
confidence: 66%
“…There is evidence that the hydrological regimes of irrigation reservoirs of Sri Lanka influence their water quality, trophic state (Nadarajah et al, 2019) and fish production (Amarasinghe & De Silva, 2015). The biological productivity and trophic status of reservoirs are known to be influenced by their hydraulic retention times (Nadarajah et al, 2019;Straškraba et al, 1995), the ratio of catchment area to reservoir extent (Nissanka et al, 2000) and the ratio of forest and shrub cover in the catchment to reservoir extent (Amarasinghe et al, 2002;De Silva et al, 2001). On the other hand, the WLF is a striking and regular feature of irrigation reservoirs because of the seasonal water releases for irrigation, which cause alternative littoral exposure and inundation.…”
mentioning
confidence: 99%